Printing and curing of conductive inks on fabric using syringe-based deposition system and oven for wearable antenna application. (January 2019) - Khirotdin, R K; Nazli, M M M N; Mahadzir, M A; Hassan, N
Abstract: Wearable antenna is part of clothing for transmitting or receiving wireless signals and due to miniaturization, the antenna required to be compact, light, cheap and almost maintenance-free. Syringe-based deposition system with conductive ink is potential to print the antenna structure on fabric as it provides flexibility and compatible with different viscosity of materials. The study is to investigate the printing and curing of conductive inks on fabric using syringe-based deposition system and oven. The effect of printing and curing parameters to morphology and conductivity of the antenna tracks were investigated. Several mechanical and electrical tests were performed to determine the hardness, adhesion and resistance level. It was observed that the antenna tracks were successfully printed according to its designated shape and printing with higher speed caused narrower antenna ink track while pressure differences influenced the thickness of the antenna tracks. The optimum printing parameters obtained was printing at 23 mm/s speed with a pressure of 1 bar to achieve the required antenna track size. The resistance level achieved was considered low at 1.6Ω curing at 160°C for 45 minutes. It was proven that the syringe-based deposition system and oven is capable of printing and curing antenna tracks on fabric.